White Matter Microstructure Alterations Associated With Paroxetine Treatment Response in Major Depression - Vieira, Rita; Coelho, Ana; Reis, Joana; Portugal-Nunes, Carlos; Magalhães, Ricardo; Ferreira, Sónia; Moreira, Pedro Silva; Sousa, Nuno; Bessa, João M. (Frontiers in Behavioral Neuroscience, 2021)
More than one third of depressive patients do not achieve remission after the first antidepressant treatment. The “watch and wait” approach used to find the most effective antidepressant leads to an increased personal, social and economic burden in society. In order to overcome this challenge, there has been a focus on studying neural biomarkers associated with antidepressant response. Diffusion tensor imaging measures have showed a promising role as predictors of antidepressant response, by pointing to pre-treatment differences in white-matter microstructural integrity between future responders and non-responders to different pharmacotherapies. Therefore, the aim of the present study was to explore whether response to paroxetine treatment was associated with differences in white-matter microstructure. Twenty drug-naïve patients diagnosed with major depressive disorder followed a 6-12 weeks treatment with paroxetine. All patients completed magnetic resonance brain imaging and a clinical assessment at baseline and 6-12 weeks after treatment. Whole-brain tract-based spatial statistics was used to explore differences in white-matter microstructural properties estimated from diffusion magnetic resonance imaging. Voxel-wise statistical analysis revealed a significant increase in fractional anisotropy and a decrease in radial diffusivity in forceps minor and superior longitudinal fasciculus in responders compared to non-responders. Alterations in white-matter integrity, specifically in forceps minor and the superior longitudinal fasciculus, are potential biomarkers of response to paroxetine treatment. These findings pave the way for personalized treatment strategies in major depression.